Kemampuan Regulasi Emosi karyawan instalasi Gizi Rumah Sakit X pengaruhnya pada Stres kerja - Inas, Farah Faiuz; Winta, Mulya Virgonita Iswindari; Nusandhani, Arumwardani (Universitas Semarang, 2023)
This study aims to empirically examine the effect of emotion regulation on work stress in employees of the Nutrition Installation of Telogorejo Hospital Semarang using quantitative research methods. The hypothesis proposed in this study is the negative influence between emotional regulation and employee work stress. The higher the emotional regulation, the lower the employee's work stress, and vice versa. The sample was taken as many as 55 employees, with saturated sampling techniques. The research data was collected using two scales, namely the Work Stress Scale and the Emotion Regulation Scale. Data analysis was carried out using a simple linear regression test processed using the SPSS (Statistical Package for Social Science) for Windows Version 20 program. The results showed that there was a negative influence between emotional regulation and employee work stress, with Y = -7.523. Thus, the hypothesis proposed in the study was accepted